2015
DOI: 10.1073/pnas.1414183112
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bilingualism on the white matter structure of the brain

Abstract: Recent studies suggest that learning and using a second language (L2) can affect brain structure, including the structure of white matter (WM) tracts. This observation comes from research looking at early and older bilingual individuals who have been using both their first and second languages on an everyday basis for many years. This study investigated whether young, highly immersed late bilinguals would also show structural effects in the WM that can be attributed to everyday L2 use, irrespective of critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
143
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(166 citation statements)
references
References 31 publications
18
143
4
1
Order By: Relevance
“…The higher mean FA value for the IFOF in these bilingual children (Mohades et al, 2012) is the opposite pattern found for young adult bilinguals in Cummine & Boliek (2013), but the same pattern as Pliatsikas et al (2015) and also for older adult bilinguals (Luk et al, 2011). At the same time, the lower mean FA value in the CC obtained for these bilingual children is opposite to the pattern obtained for older adult bilinguals in the Luk et al (2011) and Pliatsikas et al (2015) studies but in line with the pattern obtained for older bilinguals in the Gold et al (2013) study. Olsen et al (2015) also extracted the volume of the WM for the frontal, temporal, parietal and occipital lobes in both hemispheres of their sample (described above, see section 2.1.1.2).…”
Section: White Matter Studiesmentioning
(Expert classified)
See 3 more Smart Citations
“…The higher mean FA value for the IFOF in these bilingual children (Mohades et al, 2012) is the opposite pattern found for young adult bilinguals in Cummine & Boliek (2013), but the same pattern as Pliatsikas et al (2015) and also for older adult bilinguals (Luk et al, 2011). At the same time, the lower mean FA value in the CC obtained for these bilingual children is opposite to the pattern obtained for older adult bilinguals in the Luk et al (2011) and Pliatsikas et al (2015) studies but in line with the pattern obtained for older bilinguals in the Gold et al (2013) study. Olsen et al (2015) also extracted the volume of the WM for the frontal, temporal, parietal and occipital lobes in both hemispheres of their sample (described above, see section 2.1.1.2).…”
Section: White Matter Studiesmentioning
(Expert classified)
“…Furthermore, others studies support these results showing that this region is also sensitive to L2 AoA and proficiency (Grogan et al, 2012;Hosoda et al, 2013;Klein et al, 2014). Additionally, several WM structural studies also confirmed differences between bilinguals and monolinguals in the tracts connecting IFG with many other regions in the frontal lobe (including the contralateral side) and the temporal, parietal and occipital regions in the back of the brain, specifically the CC (Luk et al, 2011;Pliatsikas et al, 2015;Gold et al, 2013;Mohades et al, 2012) and the IFOF (Luk et al, 2011;Pliatsikas et al, 2015;Mohades et al, 2012;Gold et al, 2013;Cummine & Boliek, 2013). Nevertheless, although these results identified the same regions, they are contradictory because some show increases while others show decreases in the WM.…”
Section: Assessing These Findings In the Light Of Abutalebi And Greenmentioning
confidence: 67%
See 2 more Smart Citations
“…Increased FA in the inferior fronto 58 occipital fasciculus (IFOF), and decreased FA in genu and anterior corpus callosum (CC), are 59 amongst reported changes in early L2 learners among school aged children (5). Pliatsikasa and his 60 colleagues provided insights into white matter structural differences in young bilingual adults, who 61 were are sequential learners of English as second language and were highly immersed, meaning 62 that they had been using L2 on a daily basis for a long period (6 (1). Grey matter volume in these areas positively correlated with lexial efficiency and negatively 71 correlated with the age at which bilinguals had started learning a new language (7).…”
mentioning
confidence: 99%